Insights to Clinical Use of Serial Determination in Titers of Cyclic Citrullinated Peptide Autoantibodies - Toshiaki Kogure; Takeshi Tatsumi; Hiroshi Fujinaga; Atsushi Niizawa; Katsutoshi Terasawa (Hindawi Limited, 2007)
Anti-cyclic citrullinated peptide (CCP) antibody is a useful marker for the diagnosis and prognosis of rheumatoid arthritis (RA). Recently, clinical significance of follow-up in anti-CCP antibody titer has been pointed out. Thus, we investigated the serial determination in anti-CCP antibodies titer in RA patients. Six patients with RA, who were followed up for longer than 5 years, were assessed in anti-CCP antibodies and radiographs (Larsen score). Anti-CCP antibodies in frozen sera were measured using ELISA. As a result, 6 patients with RA were divided into two groups: one possessed high titers without variation, and the other was without high titers. Joint damage progressed during observation in 2 out of 3 patients with high anti-CCP titers in a retrospective assessment. In contrast, the RA patient, whose anti-CCP titer decreases although it had been high titer at baseline, did not show increase in the Larsen score. These findings suggest that it might be necessary to analyze changes in anti-CCP to predict the prognosis of joint destruction.